2009
DOI: 10.1039/b9pp00018f
|View full text |Cite
|
Sign up to set email alerts
|

Demetalation kinetics of natural chlorophylls purified from oxygenic photosynthetic organisms: effect of the formyl groups conjugated directly to the chlorin π-macrocycle

Abstract: Demetalation kinetics of natural chlorophyll (Chl) d purified from Acaryochloris marina was first studied and compared with those of Chls a and b. The demetalation rate constant of Chl d, which possessed a formyl group at the 3-position, was five-fold smaller than that of Chl a possessing a vinyl group at the same position in aqueous acetone at the proton concentration of 1.2 x 10(-3) M at 25 degrees C. In contrast, the demetalation rate constant of Chl b possessing a formyl group at the 7-position was 26 time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
29
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 46 publications
11
29
0
Order By: Relevance
“…The substitution effect of weakly electron‐withdrawing 8‐vinyl group on demetalation properties of Chls is much smaller than the strongly electron‐withdrawing 7‐formyl effects based on the comparison of the present k′ ‐value of DV‐Chl a with the reported one of Chl b under the identical acidic conditions . Such a difference between the 8‐vinyl and 7‐formyl groups would allow DV‐Phe a to function as the primary electron acceptor in PS II by in vivo demetalation of DV‐Chl a in oxygenic photosynthetic organisms.…”
Section: Resultsmentioning
confidence: 68%
See 3 more Smart Citations
“…The substitution effect of weakly electron‐withdrawing 8‐vinyl group on demetalation properties of Chls is much smaller than the strongly electron‐withdrawing 7‐formyl effects based on the comparison of the present k′ ‐value of DV‐Chl a with the reported one of Chl b under the identical acidic conditions . Such a difference between the 8‐vinyl and 7‐formyl groups would allow DV‐Phe a to function as the primary electron acceptor in PS II by in vivo demetalation of DV‐Chl a in oxygenic photosynthetic organisms.…”
Section: Resultsmentioning
confidence: 68%
“…It has been reported that electron‐withdrawing groups such as formyl and acetyl groups directly conjugated with the π‐system of cyclic tetrapyrroles slow down removal of the central metal . Such peripheral electron‐withdrawing groups would decrease the electron densities of the core nitrogen atoms, preventing electrophilic attack of protons to pyrrole nitrogen atoms.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the central magnesium was removed from natural (B)Chl molecules even by action of weak acid (Hirai et al 2009), the 3-and 7-formyl groups of Chl-d(d 0 ) and BChl-e were efficiently 18 O-labeled to give the corresponding magnesium complexes with a high 18 O-labeling degree (ca. 90%).…”
Section: Resultsmentioning
confidence: 99%